Financial Performance Analysis of Mining Company PT. Vale Indonesia Tbk. Using the Economic Value Added (EVA) Method for the 2019-2022 Period - Pole, Yogi Adnal Fathirullah; Dipoatmodjo, Tenri SP; Nurman, Nurman; Hasbiah, Siti; Aslam, Annisa Paramaswary (PT. Riset Press International, 2024)
This study aims to analyze and assess the financial performance of PT Vale Indonesia using the Economic Value Added (EVA) approach during the 2019-2022 period. The type of research used is quantitative using descriptive data. The population in this study is the financial statements of the mining company PT Vale Indonesia Tbk. for the last 4 years, namely 2019-2022. The sample of this study is the statement of financial position and comprehensive income. The data collection technique used is documentation. The data analysis technique used is Economic Value Added (EVA) analysis which consists of NOPAT, Invested Capital, WACC, and Capital Charges. The results of this study indicate that the value of Economic Value Added (EVA) at PT Vale Indonesia Tbk. period 2019-2022 is always positive (EVA> 0) so that it can be said that management is able to create economic added value for the company. The results of the analysis using the Economic Value Added (EVA) method to measure the financial performance of the mining company PT Vale Indonesia Tbk. period 2019-2022, showed that during 2019 to 2022 it was always positive (EVA> 0). Based on this, it can be said that management is able to create economic added value for the company, investors or capitalists get more investment returns than invested and creditors can get interest, this situation shows that the company has succeeded in creating value for capital owners so that it indicates good financial performance.